Leg Amputation due to Buerger’s Disease: Management with Combined Korean Medicine - Eun Sol Won; Hyun Lee; Hwa Yeon Ryu; Yong Ho Ku; Ga Hyeon Jung; Chae Hyun Park; Jae Hui Kang (Journal of Acupuncture Research, 2021)
In this Case Report, a patient with Buerger’s disease who had a leg amputation below his lower right knee and a vascular bypass of right leg, developed a wound caused by his prosthetic leg and subjective discomfort. The patient received skin flap surgery but the wound did not heal properly. He was admitted to the Korean Medicine Hospital where his wound, right leg coldness, and phantom pain were treated with combined Korean medicine. The patient was hospitalized again where he underwent micro-drilling surgery. The patient was re-admitted to the Korean Medicine Hospital where he received combined Korean medicine treatment (CKMT) and carbon arc light treatment (CALT) for his wound, leg coldness, stiffness, and hypoplasia. The temperature of his right leg increased, the numeric rating scale score for assessing pain fell from 5 to 1.5, and subjective discomfort was reduced (< 20%) suggesting this may be an effective treatment.